IMPLEMENTASI ALAT UKUR TUBUH MANUSIA MENGGUNAKAN SENSOR TANPA SENTUH MLX 90614 BERBASIS ARDUINO - Hidayatur Rakhmawati; Mamur Setianama; Ade Irma Setiawan (Journal of Informatics and Computing (RANDOM), 2024)
The signs that appear due to the covid 19 virus are abnormal human body temperatures (more than 37.5 C). Therefore, it is necessary to build a body temperature measuring device without direct contact to prevent the risk of transmission of the covid 19 virus. This study aims to apply the MLX 90614 sensor to the Arduino-based touchless human body temperature detection system.Extreme programming is suitable where the client is unsure and changes his mind frequently. Extreme programming is suitable for using an iterative approach to developing software. The stages in extreme programming are planning, design, coding and testing. The results of this study can be obtained that measuring body temperature in humans with the MLX 90614 sensor runs smoothly so that it is easier and more practical. The final average of all tests carried out on humans aged 12 years, humans aged 20 years and humans aged 30 years, can produce an average final temperature of MLX 90614 which is 36.77 0C. The final average temperature of the thermogun is 35.32 0C. Then the final average result of the difference between the MLX 90614 sensor temperature test and the thermogun temperature is 1.68. The final average result of the accuracy of the MLX 90614 sensor is 95.52%.